Arthroscopic FHL Harvest and Transfer for Neglected TA Rupture. Issue 1 (March 2016) - Vernois, Joel; Bendall, Stephen; Ferraz, Linda; Redfern, David
Abstract : Introduction: Flexor hallucis longus (FHL) transfer is an established method for repairing neglected tendo Achilles ruptures when the tendon gap is in excess of 6 cm. Some patients will have significant comorbidities—for instance, diabetes mellitus—or may be using corticosteroids, making conventional surgery more risky in terms of wound healing and soft tissue repair. In an attempt to circumvent these potential problems the authors have devised a technique to harvest FHL minimally invasively. The purpose of this paper is to describe the early results in 8 patients with 9 Achilles ruptures. Materials and Methods: Patients with a delayed tendo Achilles rupture with a gap measured by ultrasound or magnetic resonance imaging to be over 6 cm suitable for a short FHL harvest were included in this study. The posterior ankle arthroscopic approach popularized by Van Dijk was adopted to gain access to the joint and visualize the FHL tendon. A short tendon harvest was performed through a mini-incision and the FHL routed into a tunnel drilled into the os calcis. The tendon was then secured with an interference screw. The postoperative regimen included 6 weeks of protected weight-bearing in a boot, followed by physiotherapy. The outcome measures included pain, gait assessment, and the ability to perform a single heel raise at 3 months. Results: A total of 8 patients, 3 women and 5 men, aged 65 to 77 years, were included in this study. Comorbidities included high BMI in 2 (35 to 39), use of steroids in 1, and postthrombotic limb in 1. There were no wound-healing issues. Patients were pain free with normal gait. One patient was able to perform single leg raises. Conclusions: This combined technique may offer a safer surgical pathway for low-demand patients with a potential for wound problems if treated with open surgery. Level of Evidence: Diagnostic Level 4. See Instructions for Authors for a complete description of levels of evidence.